Korelasi Penguasaan Kosakata Bidang Lingkungan Hidup dan Keterampilan Menulis Teks Berita Siswa Kelas VIII SMP Negeri 2 Lengayang - Adra Permata Ingga (Universitas Negeri Padang, 2021)
The aims of this study were (1) to describe the environmental field vocabulary mastery of grade VIII SMP Negeri 2 Lengayang, (2) to describe the skills of writing news text of grade VIII SMP Negeri 2 engayang, and (3) to describe the correlation of vocabulary mastery in the environmental filed and the skills of writing news text of grade VIII SMP Negeri 2 Lengayang. This study use quantitative approach with descriptive methods. The design of this study is correlational. The population of this study is grade VIII SMP Negeri 2 Lengayang listed of the school year 2020/2021 are 135 students. The sample is determined by purposive random sampling technique of 35% of the population are 45 students. The result of this study there are three. Firstly, the vocabulary mastery of environmental field of grade VIII SMP Negeri 2 Lengayang is in good qualification (B). Secondly, the skills of writing news text of grade VIII SMP Negeri 2 Lengayang are in good qualification (B). Thirdly, there is a correlation of vocabulary mastery in the environmental filed and the skills of writing news text of grade VIII SMP Negeri 2 Lengayang with n-1 degrees of freedom at the 95% confidence level. H0 is rejected and H1 is accepted because the test results prove that tcount (6,80) is greater than ttable (1,68).